2011
DOI: 10.1007/s10845-011-0527-3
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the risk of information leakage in a two-level supply chain through optimal supplier selection

Abstract: Information leakage in supply chains is drawing more and more attention in supply chain management. Unlike existing research, which usually focuses on the effect of information leakage on the supply chain's material and information flow, this paper aims to evaluate and mitigate the risk of information leakage. First, we formulate the problem of information leakage caused by inferences in a twolevel supply chain where potential competition may exist between a supplier and the manufacturer. Second, we propose a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…The supplier's incentive to prevent information leakage is that they could yield higher profit for the supplier depending on their economies of scale. Zhang et al (2012) take a different approach to resolve the information leakage problem. Rather than focusing on the contracts between the parties, they investigate the dynamics that cause the problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The supplier's incentive to prevent information leakage is that they could yield higher profit for the supplier depending on their economies of scale. Zhang et al (2012) take a different approach to resolve the information leakage problem. Rather than focusing on the contracts between the parties, they investigate the dynamics that cause the problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hallikas et al [98] focused the risks on supplier relationships and networks, Neiger et al [99] determined process-based risks in supply chain based on Value-Focused Process Engineering (VFPE), Kleindorfer et al [100] concentrated on the disruption risks in supply chain. However, Zhang et al [101] stated that current research ignore general risk sources that affect supply chains in a less visible manner, such as information leakage. According to such analysis, Sun et al [10] identified the risks of information leakage in collaborative design chain environment.…”
Section: Risk Managementmentioning
confidence: 99%
“…Khan et al [106] addressed the importance of the impact of product design on supply chain risk based on an in-depth longitudinal case study of a major UK retailer. For the purpose of intellectual property protection, Zhang et al [101] mitigated the risk of confidential information leakage through optimal supplier selection.…”
Section: Risk Managementmentioning
confidence: 99%
“…was considered by Gürler and Parlar (1997). Zhang et al (2011) presented the model that aims to evaluate and mitigate the risk of information leakage. First, we formulate the problem of information leakage caused by inferences in a two-level supply chain where potential competition may exist between a supplier and the manufacturer.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%